2011
DOI: 10.5372/1905-7415.0504.070
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication (Original). Visual outcome in open globe injuries in Thailand: a prospective study

Abstract: Patients were interviewed at first visit and followed-up for six months. The Birmingham Eye Trauma Terminology was used to classify types of injuries. Demographic data, cost of treatment, length of stay, and predictive factors (initial visual acuity, presence of relative afferent pupillary defect, hyphema, vitreous hemorrhage, intraocular foreign bodies, retinal detachment, time-duration to surgery, and wound length) were assessed. Results: Fifty-two out of 60 eyes were included. Most (82.7%) of patients were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Similar to other studies worldwide, our study showed that boys were more susceptible to suffer from open globe injuries than girls [2][3][4][5][6][7][8][9][10][11]. The male predisposition could be explained by the boy's tendency to involve in more dangerous activities that make them prone to the risk of experiencing a traumatic eye injury.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar to other studies worldwide, our study showed that boys were more susceptible to suffer from open globe injuries than girls [2][3][4][5][6][7][8][9][10][11]. The male predisposition could be explained by the boy's tendency to involve in more dangerous activities that make them prone to the risk of experiencing a traumatic eye injury.…”
Section: Discussionsupporting
confidence: 86%
“…The variability among age groups may be the result of the differences in nurturing, lifestyle, and caregiver's education. Our study also demonstrated that injuries in children majorly arose at home (67.4%), as opposed to adults whose injuries commonly occur at a workplace [4,8]. Interestingly, only 17.4% of the children's eye injuries in our study happened at school despite children spending more time at school than at home, similar to the result of Sul et al [6] and Tok et al [10] that showed most of the injuries occurred at home and there were a little number of the injuries at school (4.4% and 8.5%, respectively).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations